The Firegator - Leland, Debbie; Rife, Ann Hollis (College Station, Tex. : Wildflower Run Pub., 2002)
At the Bryan, Texas, fire station, where his family lives, Charlie finds an alligator that follows him like a puppy, causing trouble wherever they go, until the night the alligator wakes the town to an emergency.